2022
DOI: 10.1126/sciadv.abm5504
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of RNA polymerase II pausing and elongation progression by PAF1

Abstract: Pleiotropic transcription regulator RNA polymerase II (Pol II)–associated factor 1 (PAF1) governs multiple transcriptional steps and the deposition of several epigenetic marks. However, it remains unclear how ultimate transcriptional outcome is determined by PAF1 and whether it relates to PAF1-controlled epigenetic marks. We use rapid degradation systems and reveal direct PAF1 functions in governing pausing partially by recruiting Integrator-PP2A (INTAC), in addition to ensuring elongation. Following acute PAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 88 publications
(126 reference statements)
4
28
0
Order By: Relevance
“…With the help of DSIF, NELF contributes to the stabilization of the first but not the second pausing [ 52 , 53 ], with its depletion resulting in the downstream shift of Pol II to the second pausing sites around the +1 nucleosome dyad. The stabilization of Pol II at the second pausing sites is aided by the pausing and elongation regulator PAF1 complex (PAF1C) and probably chromatin remodelers [ 54–56 ], whereas Pol II release from the second pausing sites requires factors such as P-TEFb and MYC [ 52 , 53 , 57 ].…”
Section: Spt5 Function In Pausingmentioning
confidence: 99%
See 3 more Smart Citations
“…With the help of DSIF, NELF contributes to the stabilization of the first but not the second pausing [ 52 , 53 ], with its depletion resulting in the downstream shift of Pol II to the second pausing sites around the +1 nucleosome dyad. The stabilization of Pol II at the second pausing sites is aided by the pausing and elongation regulator PAF1 complex (PAF1C) and probably chromatin remodelers [ 54–56 ], whereas Pol II release from the second pausing sites requires factors such as P-TEFb and MYC [ 52 , 53 , 57 ].…”
Section: Spt5 Function In Pausingmentioning
confidence: 99%
“…Structural comparison of NELF- and PAF1C-containing Pol II complexes reveals steric clashes between NELF and PAF1C, thus eliciting a plausible model that the shift of Pol II from the first to the second pausing sites is accompanied by a substantial change in the composition of Pol II complex, such as the replacement of NELF by PAF1C [ 15 , 54 , 58 ]. Different from the eviction of NELF during this transition, DSIF remains with Pol II at the second pausing site ( Figure 2a ).…”
Section: Spt5 Function In Pausingmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro transcription reactions with purified factors showed that human Paf1C (hPaf1C) can stimulate transcription elongation on chromatin templates in cooperation with TFIIS (11). More recently, depletion of individual Paf1C subunits, including Paf1 and Rtf1, from human or mouse cell lines has revealed positive effects of the complex on elongation rate and Pol II processivity as well as context-dependent effects on promoter proximal Pol II pausing (12)(13)(14)(15)(16)(17). The ability of hRtf1 to stimulate Pol II elongation rate in vitro involves an intimate contact between the hRtf1 latch domain and the Pol II catalytic center (5).…”
Section: Introductionmentioning
confidence: 99%